Selected recreational preferences of juveniles in selected residential treatment institutions in Wisconsin - Holland, Jearold (My University, 1982)
The purpose of this study was to determine the selected recreational preferences of juveniles in selected residential treatment institutions in Wisconsin. There were 406 males and females selected as subjects from 19 residential treatment institutions. A questionnaire was used to obtain the data needed for the study. The study was conducted from November 1980 to February 1981. Questionnaires with instructions for administering the questionnaire were mailed to 30 residential treatment institutions in Wisconsin. Nineteen institutions were represented in the study with six institutions requesting not to participate. The remaining five institutions did not reply. The questionnaire consisted of two parts. The first part asked for the age, sex, race and institution in which the subject resided. The second part consisted of 49 activities with columns to be checked indicating the preference towards each activity. The results of the study indicated a preference toward a variety of activities. Most prevalent among the activities preferred was a desired interest for social activities, for example: pool, bowling, parties, picnics, camping, frisbee, swimming, skiing, roller skating, ice skating and ping pong. Also noted in the results was a preference toward activities considered adventurous or challenging, for example: backpacking, skiing, horseback riding, camping, canoeing and fishing. Activities considered as creative received high ranking, for example: art, arts and crafts, reading and group talks.
Keywords: Recreation and juvenile delinquency -- Research; University of Wisconsin--La Crosse -- Employees